EVALUATION OF PUMP MAINTENANCE PERFORMANCE USING OVERALL EQUIPMENT EFFECTIVENESS AND SIX BIG LOSSES - Halima Tus'sadiah; Afif Fawa Idul Fata; Priyo Ari Wibowo (FEBI UIN Sunan Gunung Djati Bandung, 2026)
Equipment reliability is an essential factor in maintaining production continuity and operational efficiency in manufacturing industries. Frequent failures of Pump 402 and Pump 502 at PT XYZ resulted in increased downtime and reduced production performance. This study aimed to evaluate maintenance effectiveness using the Overall Equipment Effectiveness (OEE) method and identify the dominant causes of equipment losses through the Six Big Losses approach. A quantitative descriptive method was employed using maintenance reports, downtime records, production data, operating hours, and machine maintenance data collected during the observation period. OEE was calculated based on three performance indicators, namely Availability, Performance, and Quality, while Six Big Losses analysis was used to determine the major sources of equipment inefficiency. The results indicated that the average OEE value was below the world-class standard of 85%, suggesting that maintenance performance still requires improvement. Reduced Speed Losses and Equipment Failure Losses were identified as the dominant contributors to productivity losses. The primary causes included bearing damage, mechanical seal leakage, shaft misalignment, and failures of internal pump components. Based on these findings, improvements are recommended through strengthening preventive maintenance programs, conducting periodic equipment inspections, improving spare-part management, and standardizing maintenance procedures. These recommendations are expected to reduce downtime, improve equipment reliability, and enhance overall production performance.